PEMETAAN GEOLOGI NIKEL LATERIT DAERAH SP UNIT 25 DAN SEKITARNYA KECAMATAN TOILI BARAT, KABUPATEN BANGGAI, PROPINSI SULAWESI TENGAH - -, Geni Dipatunggoro (Fakultas Teknik Geologi Universitas Padjadjaran, 2010)
The morphology of investigated area is a flat area and hilly area at elevation reaching 20 meters above the sea level. The lateritic nickel is a residual soil from weathering, resulting from serpentinite, hasburgite and dunite being ultramafic complex according to the geologic map of Batui sheets, Celebes.The extent of investigation is 8000 hectare as the permit from the regency of Banggai, and the thichness of nickel bearing lateritic soil averaging 2 meters, and therefore is roughly estimated 160.000.000 cubic meters. If the specivic gravity of lateritic soil is 2.6 and nickel content average 0.8 %, the reserve of lateritic nickel is will be 160,000,000 M³x 2.6 x 0.8% = 3,328,000 Tons. It is suggested to be mined by open pit method because the lateritic soil on the surface with only averaging thichness of soil 2 meters.